The Implementation of Project-Based Learning Based on The Utilization of Telang Flowers to Enhance Students’ Creativity - Yudesta Erfayliana; Oktaria Kusumawati; Tegar Arif Saputra (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2026)
The low creative thinking ability of elementary school students requires learning that is more contextual, active, and grounded in direct experience. This study aims to describe the implementation of Project-Based Learning using blue pea flowers to strengthen students’ creativity at SD Alam Lampung. The study employed a qualitative approach with a case study design. Informants included the principal, teachers, students, and parents selected purposively. Data were collected through observation, semi-structured interviews, documentation, and analysis of students’ products, then analyzed through data reduction, data display, and conclusion drawing. Findings show that PjBL based on blue pea flowers engaged students in observing, designing, processing, producing, presenting, and reflecting on their products. Students’ creativity appeared in fluency, flexibility, originality, and elaboration through ecoprint, blue pea bika ambon, blue pea pancakes, milk pudding, and lemon blue pea drinks. The study concludes that blue pea flowers can serve as a local project medium for strengthening creativity. The implication is that teachers can use nearby natural materials as creative, collaborative, ecological, and meaningful learning resources aligned with Pancasila Student Profile values. Future studies should broaden school contexts and develop quantitative creativity instruments for stronger empirical evidence.